The Role Of Agility In The Relationship Between Use Of Management Control Systems And Organizational Performance: Evidence From Korea And Japan - Lee, Sangwan; Lee, Dasom; Kim, Soonkee; Lee, Gunyung (Journal of Applied Business Research, 2017)
This study investigates the role of agility in the relationship between use of management control systems (MCS) and organizational performance by proffering the association of agility, use of MCS, and organizational performance. Using survey data collected from 185 large Korean and Japanese manufacturing companies, we analyze proposing relationships with partial least squares (PLS) structural equation approach. The result shows that diagnostic use of MCS shows no significant relationship with agility, while interactive use of MCS is positively associated with agility. Agility positively affects organizational performance, which implies that characteristics of agility are necessary to overwhelm rivals under rapidly changing environment. This study is one of the first studies that empirically examine the role of agility as an organizational capability in the relationship between MCS and organizational performance with data collected from two different countries.
Keywords: Agility; Organizational Capability; MCS; PMS; Budget Systems